Pengaruh Teknologi Informasi Dan Manajemen Aset Terhadap Kinerja Rumah Sakit Dengan Optimalisasi Aset Sebagai Variabel Intervening Pada Rumah Sakit Vertikal (BLU) Kementerian Kesehatan - Perwitasari, Nurdiyanti; Widyastuti, Tri; Bahri, Syamsul (JURNAL EKONOMI, MANAJEMEN, BISNIS, DAN SOSIAL (EMBISS), 2023)
This 2022 research entitled The Effect of Information Technology and Asset Management on Hospital Performance with Asset Optimization as an Intervening Variable at the Vertical Hospital (BLU) of the Ministry of Health. The purpose of this study is to analyze whether there is a significant influence between Information Technology and Asset Management on Hospital Performance based on the Director General of Treasury No.24 of 2018 regarding guidelines for evaluating the performance of BLU in the health service sector, with Asset Optimization as an Intervening Variable in Vertical Hospitals (BLU). Ministry of Health. The independence of the financial management of the Vertical Hospital to become a BLU is the same as how the Vertical Hospital can better utilize the assets that are currently available but are not yet optimal in terms of management. So there is a need for asset optimization at the Vertical Hospital so that it can provide more benefits for the general public as well as benefits for the Vertical Hospital within the Ministry of Health, especially in facing the current pandemic conditions which must be more prepared in terms of service (asset optimization) as a form of service readiness. Health when the pandemic returns. The research method used is Ex Post Facto Causality Research, with this type of research based on a time approach using a cross-sectional approach. Data management in this study will use PLS 3.2.6 Smart Software Structural Equation Modeling (SEM) Variance Based SEM or Partial Least Square (PLS) is a method used to cover the weaknesses contained in the regression method. The sampling technique used is Non-Probability Sample / Purposive Sampling which uses a total sample of 34 people, representing 34 BLU Vertical Hospitals. In the whole of this study, the biggest influence on the t-test is the influence of Asset Management on Asset Optimization (t count of 9.275 is greater than t table of 1.96), which has a positive and significant effect